The blue max [videorecording (DVD)] - Guillermin, John, 1925-2015; Peppard, George; Mason, James, 1909-1984; Andress, Ursula, 1936-; Kemp, Jeremy, 1934-2019-; Vogler, Karl Michael, 1928-2009; Diffring, Anton, 1918-1989; Hunter, Jack D. (20th Century Fox Home Entertainment, 2003)
A low-born infantryman becomes a pilot during World War I, almost deliberately stepping on the sensibilities of his aristocratic comrades in the process. A national hero, he wins the Blue Max, the highest award that can be bestowed upon an aviator. His fame is exploited by a general, who tolerates the affair between the pilot and the general's wife. The canny general knows that, eventually, the pilot will become expendable, and a "heroic" death can be arranged.